Pengaruh Video Edukasi Terhadap Pengetahuan Ibu Tentang Pijat Pada Bayi di Puskesmas Tempunak Tahun 2025 - Putri; Novita Dewi Puspita; Selasih Putri Isnawati Hadi (Journal of Midwifery Science: Basic and Applied Research, 2026)
Knowledge is paramount in implementing an action because actions based on knowledge are, in principle, better. Husbands who have good knowledge about stunting prevention can provide support to mothers by meeting the nutritional needs of pregnant and breastfeeding mothers. Husband's support is the most important element in helping individuals solve problems. With support, self-confidence will increase and motivation to face problems will increase. Family support, especially husbands, is very dominant in providing moral and physical assistance during pregnancy. The purpose of this study was to determine the relationship between husbands' knowledge levels and support for pregnant women in stunting prevention efforts. This type of research is quantitative with an analytical design and a cross-sectional approach. This study was conducted at the Blora Community Health Center UPTD with a population of 92 husbands of pregnant women who underwent examinations in August 2024. The sampling technique used consecutive sampling and obtained a sample of 75 people. The research instrument used a knowledge and support questionnaire. Data analysis was performed using the Fisher's Exact test with a 5% error rate. The results showed a relationship between husbands' knowledge and support for pregnant women in stunting prevention efforts with a p-value of 0.002 <0.05. There is a need to increase counseling for pregnant women about preventing stunting by involving the family, especially the husband.